Adapting a drinking water treatment technology for arsenic removal to the context of a small, low-income California community. (1st October 2021) - Glade, Sara; Bandaru, Siva RS; Nahata, Mohit; Majmudar, Jay; Gadgil, Ashok
Highlights: Fe-EC was field-tested for its arsenic removal suitability in rural California. Arsenic in groundwater was reduced from 150 µg/L to below 10 µg/L in all experiments. Adding H2 O2 externally in the Fe-EC process shortened electrolysis time by 28 fold. Waste was characterized per California regulations for planning waste management. Increasing current density to eliminate electrode cleaning, needs further research. Abstract: Small, low-income, and rural communities across the United States are disproportionately exposed to arsenic contaminated drinking water because existing treatment solutions are too expensive and difficult to operate. This paper describes efforts to overcome some barriers and limitations of conventional iron electrocoagulation (Fe-EC) to enable its use in the rural Californian (U.S.) context. Barriers and limitations of Fe-EC's application in rural California considered in this work include: 1) Frequent labor intensive electrode cleaning is required to overcome rust accumulation, 2) Electrolysis durations are long, reducing throughput for a given system size, and 3) Waste needs compliance with California standards. We report results from an investigation for overcoming these limitations via a field trial on a farm in Allensworth, a small, low-income, rural community in California. Our strategies to overcome each of the above barriers and limitations are respectively, 1) operating the Fe-EC reactor at high current density to result in sustained Fe production, 2) operating at high charge dosage rate with external H2 O2, and 3) characterization of the arsenic-laden waste, and are discussed further in the paper. Main findings are: (1) Fe-EC removed arsenic consistently below the federal (and state) standard of 10 µg/L, (2) high current density failed to sustain Fe production whereas low current density did not, (3) electrolysis time decreased from > 1 hour to < 2 min with H2 O2 dosing of 5 mg/L at higher charge dosage rates, (4) dilution of As-sludge is required to comply with State's non-hazardous waste status, and (5) discrepancies were observed between lab and field results in using current density to overcome labor-intensive electrode cleanings. Finally, implications of overcoming limitations to scale-up of Fe-EC in relevant California communities are discussed.